First report of Ceratocystis fimbriata causing wilt disease of soursop in South Sumatra, Indonesia - RAHMAT PRATAMA; AHMAD MUSLIM; SUWANDI SUWANDI; SUPARMAN SHK (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Pratama R, Muslim A, Suwandi S, Suparman Shk. 2023. First report of Ceratocystis fimbriata causing wilt disease of soursop in South Sumatra, Indonesia. Biodiversitas 24: 6711-6721. Ceratocystis fungus is a well-known pathogen that frequently attacks agroforestry plants. Symptoms of canker and wilt in soursop plants (Anona muricata L.) similar to those of ceratocystis disease with 57-100% mortality were first observed in South Sumatra, Indonesia in 2021. This study aimed to describe the symptomatology of the new disease and characterize isolates of Ceratocystis fimbriata Ellis & Halst. obtained from diseased soursop plants. The identification of this pathogen involved a comprehensive polyphasic analysis, which combined morphological and molecular characteristics derived from specific genomic regions (ITS and ?-tubulin). Morphological and phylogenetic analysis revealed that all pathogen isolates were identified as C. fimbriata. All the population showed uniform morphology, comprising ITS5 and ITS7b haplotypes. The pathogenicity test indicated that C. fimbriata induced similar symptoms similar to natural symptoms, resulting in mortality rates of 50-90%. The results of pathogenicity tests of A. muricata isolates showed their high pathogenicity toward other Ceratocystis hosts plants, including Artocarpus heterophyllus Lam. and Acacia mangium Willd. These tests resulted in the death rates of 15-50% and 75-100%, respectively, which closely resembled the pathogenicity observed on A. muricata. Both isolates of the ITS5 haplotype exhibited nearly identical pathogenicity on the three hosts, while ITS7b displayed higher aggressiveness. This is the the first report of C. fimbriata as a causal agent of wilt in soursop trees in Indonesia and worldwide, highlighting the importance of understanding this pathogen and its management to mitigate its impact on agroforestry plants.